RELATIONSHIP BETWEEN DELAYED PROMOTION AND JOB STRESS: A QUANTITATIVE STUDY OF CIVIL SERVANTS IN ENUGU STATE, NIGERIA - Ojobor, Mercy L. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Several disparate studies have highlighted the correlation between job promotion and workers' performance, commitment, and motivation. However, little is known about delayed promotion and employee stress. The study examined the correlation between delayed promotion and job stress. Two hundred and thirty-three civil servants were drawn from the Enugu state civil service and completed the self-report instrument used for data collection. The association between delayed promotion and job stress was analyzed using Pearson's product-moment correlation. Preliminary studies revealed that the association was linear, with both variables normally distributed (p >.05) and no outliers, as shown by the Shapiro test. Wilk's There was a modest positive connection between delayed promotion and job stress that was statistically significant, r (231) = .36, p < .001. Most importantly, it is observed that delayed promotion explained about 13.1% of the variation in employees' job stress.